Answer:
49
Step-by-step explanation:
delta math said it
![\bf \begin{cases} f(x)=\cfrac{x}{x-9} \\ \quad \\ g(x)=\cfrac{-x}{x-3} \end{cases}\qquad f(x)+g(x)\implies \cfrac{x}{x-9}+\cfrac{-x}{x-3}](https://tex.z-dn.net/?f=%5Cbf%20%5Cbegin%7Bcases%7D%0Af%28x%29%3D%5Ccfrac%7Bx%7D%7Bx-9%7D%0A%5C%5C%20%5Cquad%20%5C%5C%0Ag%28x%29%3D%5Ccfrac%7B-x%7D%7Bx-3%7D%0A%5Cend%7Bcases%7D%5Cqquad%20f%28x%29%2Bg%28x%29%5Cimplies%20%5Ccfrac%7Bx%7D%7Bx-9%7D%2B%5Ccfrac%7B-x%7D%7Bx-3%7D)
get their LCD, like you'd with any other fractions, and add them up
Adjacent angles :
IGJ and IGH
KGL and LGM
vertical angles :
JGK and HGM
IGJ and MGL
hope this helps
101.65 x .30= 30.50 saving
so take 101.65 - 30.50= 71.15